Pembacaan Heuristik Dan Hermeneutik Untuk Menggali Makna Lagu Pretender Karya Hige Dandism (Kajian Semiotika Riffaterre): Heuristic and Hermeneutic Reading to Explore the Meaning of the Song Pretender by Hige Dandism (Riffaterre's Semiotic Study) - Erika Selphie Damayanti; Mintarsih; Sopaheluwakan, Yovinza Bethvine (Undiksha Press, 2025)
The song titled Pretender with Japanese verse caused multiple interpretations from various blogs and videos. With the implied meaning of